The Influence of Exchange Rate, Leverage, Intangible Assets and Tunneling Incentives on A Company's Decision To Conduct Transfer Pricing (Empirical Study of Manufacturing Companies Listed on the BEI 2019-2021) - Citra Nugraheni Kinanti Raharjo; Fauzan, Fauzan (Dinasti International Journal of Economics, Finance & Accounting, 2024)
In this era of globalization and increasing cross-border activity, transfer pricing is a topic that is increasingly discussed and of concern to multinational companies and tax authorities.  Several countries have adopted transfer pricing regulations.  This research aims to analyze exchange rates, leverage, intangible assets and tunneling incentives on company decisions in carrying out transfer pricing.  The dependent variable in this research is transfer pricing.  The independent variables in this research are exchange rates, leverage, intangible assets and tunneling incentives.  The financial or annual reports of manufacturing businesses listed on the Indonesia Stock Exchange for the 2019–2021 period serve as the secondary data source for this study.  Choosing the sample by use of the purposive sampling technique.  This study used 33 companies and 99 data points as its sample.  The results of this research found that (1) exchange rates have no effect on transfer pricing, (2) leverage has an effect on transfer pricing, (3) intangible assets have an effect on transfer pricing, and (4) tunneling incentives have no effect on transfer pricing.  influence on transfer prices.